Separation of Revenue and Expenditure increases first contact care in community health centers among community residents. Issue 2 (1st June 2013) - Guo, Hong; Liang, Xiaoyun; Jin, Chenggang
Abstract : Objective: To evaluate the impact of Separation of Revenue and Expenditure (SRE) on the first contact care in community health centers (CHCs) among community residents. Methods: Data was obtained through questionnaire survey before and after the pilot. Residents who visited CHCs within two weeks before the conduction of the surveys were included in this study. This study employed a pre-post quasi-experiment design and multiple regression models were specified based on the Andersen theoretical framework. Results: Multiple logistic regression analysis showed that the rate of first contact care in CHCs increased by 28. 3% ( P =0. 000). Conclusions: SRE has increased the first contact care in CHCs among the community residents.